Thermal Processes at Electron-Beam Treatment of Yttrium-Stabilized Zirconium Dioxide Ceramics; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Ivanov Yu. F. Yuriy Fedorovich; Tolkachev O. S. Oleg Sergeevich; Petrikova E.; Ivanova O. P. Olga Petrovna; Ikonnikova I.; Petyukevich M. S. Mariya Stanislavovna (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen